2013
DOI: 10.4049/jimmunol.1102725
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 Triggering with Polyuridylic Acid Promotes Cross-Presentation in CD8α+ Conventional Dendritic Cells by Enhancing Antigen Preservation and MHC Class I Antigen Permanence on the Dendritic Cell Surface

Abstract: ssRNA can interact with dendritic cells (DCs) through binding to TLR7, inducing secretion of proinflammatory cytokines and type I IFN. Triggering TLR7 enhances cross-priming of CD8+ T cells, which requires cross-presentation of exogenous Ag to DCs. However, how TLR triggering can affect Ag cross-presentation is still not clear. Using OVA as an Ag model, we observed that stimulation of TLR7 in DCs by polyuridylic acid (polyU), a synthetic ssRNA analog, generates a strong specific cytotoxic response in C57BL/6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 91 publications
3
37
0
Order By: Relevance
“…In parallel, studies have also demonstrated that DCs activated with TLR7 agonists resulted in enhanced antigen cross-presentation to CD8 + T cells [10,39]. In line with the previous observations [10,39], the two new TLR7 agonists, particularly J4, could also efficiently promote antigen-specific CD8 + T cell responses, although they both induced lower levels of cytokine expression in the APCs that were tested. However, these two new TLR7 agonists as well as R848 and CL075 were equally potent at upregulating the expression of costimulatory molecules that could contribute to the enhanced CD8 + T cell responses.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In parallel, studies have also demonstrated that DCs activated with TLR7 agonists resulted in enhanced antigen cross-presentation to CD8 + T cells [10,39]. In line with the previous observations [10,39], the two new TLR7 agonists, particularly J4, could also efficiently promote antigen-specific CD8 + T cell responses, although they both induced lower levels of cytokine expression in the APCs that were tested. However, these two new TLR7 agonists as well as R848 and CL075 were equally potent at upregulating the expression of costimulatory molecules that could contribute to the enhanced CD8 + T cell responses.…”
Section: Discussionsupporting
confidence: 54%
“…This is because TLR7 is known to recognize viral single-stranded RNAs (ssRNAs) and thus activate signaling cascades in APCs followed by the generation of viral antigen-specific CD8 + T cells that play a critical role in the clearance of viruses [37,38]. In parallel, studies have also demonstrated that DCs activated with TLR7 agonists resulted in enhanced antigen cross-presentation to CD8 + T cells [10,39]. In line with the previous observations [10,39], the two new TLR7 agonists, particularly J4, could also efficiently promote antigen-specific CD8 + T cell responses, although they both induced lower levels of cytokine expression in the APCs that were tested.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, TLR9 agonists have been shown to increase TAP-independent Ag presentation by MHC class I (42). Moreover, TLR7 ligation limits Ag degradation in endophagosomal compartments and enhances the formation of peptide/MHC class I complexes on DCs (43). In this report, we further investigated whether the endosomal-associated protein Rab7 could be upregulated by TLR2 ligation.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, we found that in mice immunized with OVA, SMIP2.1 increases the number of APCs (CD8a ¡ DCs, CD8a C DCs, macrophages, inflammatory monocytes and B cells) that take up antigen and migrate to LNs. We can then speculate that this increased uptake results in enhanced cross-presentation by both CD8a ¡ and CD8a C DCs populations as observed in the in vitro assays and it may It has been described that only CD8a C CD11c C DCs can cross-present in mice 39,40 and most of the adjuvants that can stimulate cross-presentation act exclusively on this population, 41,16 which represents only~20% of the conventional DCs in mouse spleen. 27 The ability of SMIP2.1 to activate cross-presentation also in the CD8a ¡ subset offers the advantage of acting on a larger cell population.…”
Section: Discussionmentioning
confidence: 99%